A comparison of the revised Delirium Rating Scale (DRS–R98) and the Memorial Delirium Assessment Scale (MDAS) in a palliative care cohort with DSM–IV delirium. Issue 4 (3rd July 2014) - O'Sullivan, Roisin; Meagher, David; Leonard, Maeve; Watne, Leiv Otto; Hall, Roanna J; Maclullich, Alasdair M.J.; Trzepacz, Paula; Adamis, Dimitrios
Abstract Objective: Assessment of delirium is performed with a variety of instruments, making comparisons between studies difficult. A conversion rule between commonly used instruments would aid such comparisons. The present study aimed to compare the revised Delirium Rating Scale (DRS–R98) and Memorial Delirium Assessment Scale (MDAS) in a palliative care population and derive conversion rules between the two scales. Method: Both instruments were employed to assess 77 consecutive patients with DSM–IV delirium, and the measures were repeated at three-day intervals. Conversion rules were derived from the data at initial assessment and tested on subsequent data. Results: There was substantial overall agreement between the two scales [concordance correlation coefficient (CCC) = 0.70 (CI95 = 0.60–0.78)] and between most common items (weighted κ ranging from 0.63 to 0.86). Although the two scales overlap considerably, there were some subtle differences with only modest agreement between the attention (weighted κ = 0.42) and thought process (weighted κ = 0.61) items. The conversion rule from total MDAS score to DRS–R98 severity scores demonstrated an almost perfect level of agreement (r = 0.86, CCC = 0.86; CI95 = 0.79–0.91), similar to the conversion rule from DRS–R98 to MDAS. Significance of results: Overall, the derived conversion rules demonstrated promising accuracy in this palliative care population, but further testing in other populations is certainly needed.